The importance of Techmer's "Internationale Zeitschrift für Allgemeine Sprachwissenschaft" in the development of general linguistics : an essay - Koerner, E. F. K. (Amsterdam studies in the theory and history of linguistic science. Studies in the history of linguistics ;, 1973)
Techmer's Internationale Zeitschrift für Allgemeine Sprachwissenschaft (1884-1890) served, at a time of neogrammarian domination in the linguistic scene of the late 19th century, as an international forum for the discussion of general linguistics topics, the Humboldtian philosophy of language, and the promotion of non-Indo-European linguistic research. This essay starts with information on the founder and sole editor of the journal, Friedrich Techmer, then analyzes the most significant contributions to the journal, surveying in the same part the range of publications as well as the.